Milk secretion in the rabbit: changes during lactation and the mechanism of ion transport. - Peaker, M (1975)
Changes in the yield and composition of milk and in the permeability of the mammary epithelium to labelled disaccharides and ions have been studied during lactation in rabbits of the Dutch breed. 2. Milk yield increased to reach a peak on day 20 of lactation and then declined, but by 30-32 days the yield was still relatively high. Milk [protein] and [fat] increased in late lactation; [Na] and [Cl] decreased from early to established lactation (11-14 days) and then increased, whereas milk [K] and [lactose] showed an inverse pattern to that displayed by[Na] and [Cl]. 3. At all stages of lactation [Na] and [Cl] were both inversely related to milk [lactose] while [K] showed a positive correlation. 4. Labelled lactose and sucrose were found to cross the mammary epithelium at all stages but in increased amounts during late lactation. Sucrose entry from blood into milk was positively correlated with milk [Na], and inversely correlated with [K] and [lactose]. 5. The entry of (24)Na and (36)Cl into milk from blood paralleled the changes in milk [Na] and [Cl]. 6. Intracellular ionic composition determined in vitro was similar for [Na] and [K] in both established (11-14 days) and late (25-28 days) lactation, but [Cl] was higher in late lactation. 7. Intracellular potentials recorded in vivo were -31 mV (mean) and -36 mV in established and late lactation respectively. Transepithelial p.d. was close to zero at both stages. 8. It is suggested that ions and lactose and other small molecules can cross the mammary epithelium by a paracellular, as well as by a transcellular route, throughout lactation and that the paracellular pathway is increased in late lactation. 9. The site of the proposed paracellular pathway and the implications of such a pathway's presence on ion transport are discussed, and a scheme is suggested to account for the ionic composition of milk in this species.